Review on dynamic and quasi-static buffeting response of transmission lines under synoptic and non-synoptic winds. (1st April 2016) - Aboshosha, Haitham; Elawady, Amal; El Ansary, Ayman; El Damatty, Ashraf
Highlights: This study reviews the literature on the buffeting dynamic and quasi-static response of Transmission Lines. The study focuses on the response under synoptic and non-synoptic (downburst) wind. For the synoptic wind, four design codes are considered for comparison. Limitations and gaps in the current structural design codes are identified. Recommendations to fill out those gaps are provided. Abstract: This study reviews the literature on the dynamic response of a Transmission Line (TL) system under synoptic wind (conventional atmospheric boundary layer) as well as non-synoptic wind loading (downbursts). Gust-induced response for the conductors and the towers are covered and the limitations in the current structural design codes for wind loading are identified. Three main sections are considered in this study covering synoptic wind loading, downburst, and main conclusions and recommendations. For the case of synoptic wind events, four design codes (ASCE 74 2010, AS/NZS 2010, BS 2001, IEC 2003) specialized in TLs are considered for comparison. Using the ASCE 74 as a datum for normalization, a code ratio ( CR ) is evaluated for various parameters to assess the discrepancy between the codes. The code ratio for conductor forces CRFc is found to be ranging between 0.81 and 1.44. For tower forces code ratio CRFt, a discrepancy range of 0.68 and 1.85 is noticed. The study highlights the main reasons behind these discrepancies. For the case of downbursts, the study reveals that the event's size and its relative location to the tower lead to a number of critical load cases that need to be considered. The study provides important design considerations for both synoptic and non-synoptic winds. At the end of the study, a list of the main gaps existing in current design codes and recommendations to fill out these gaps is provided.